Ethnodemographic characterization of stroke incidence and burden of disease in hospital discharge records in Ecuador - Carrington, Sarah J.; Romero-Alvarez, Daniel; Coral-Almeida, Marco; Vela, Andrea; Henríquez-Trujillo, Aquiles Rodrigo; Mascialino, Guido (Frontiers in Neurology, 2023)
Introduction Stroke is the second most common cause of death and disability-adjusted life years (DALYs) globally. However, the incidence and impact of stroke by ethnicity and gender is frequently distinct. This is particularly the case in Ecuador where geographic and economic marginalization are often correlated with ethnic marginalization and the extent to which females lack the same opportunities as their male counterparts. The aim of this paper is to investigate the differential impacts in terms of stroke diagnosis and burden of disease by ethnicity and gender, using hospital discharge records over the years 2015–2020. Methods This paper calculates stroke incidence, and fatality rates using hospital discharge and death records over the years 2015–2020. The DALY package in R was employed to calculate the Disability Adjusted Life Years lost due to stroke in Ecuador. Results The results show that while the incidence rate of stroke in males (64.96 per 100,000 persons-year) is higher than that for females on average (57.84 per 100,000 persons-year), males accounted for 52.41% of all stroke cases and 53% of all surviving cases. Thus, hospital data suggests that females had a higher death rate when compared to males. Case fatality rates also differed significantly by ethnicity. The highest fatality rate corresponded to the Montubio ethnic group (87.65%), followed by Afrodescendants (67.21%). The estimated burden of disease of stroke calculated using Ecuadorian hospital records (2015–2020) varied from 1,468 to 2,991 DALY per 1,000 population on average. Discussion Differences in the burden of disease by ethnic group are likely to reflect differential access to care by region and socio-economic group, both of which are frequently correlated with ethnic composition in Ecuador. Equitable access to health services remains an important challenge in the country. The gender discrepancy in fatality rates suggests that there is a need for targeted educational campaigns to identify stroke signs early, especially in the female population.